2013
DOI: 10.1111/1365-2664.12092
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the relative resilience of subarctic lakes to global change: redundancies of functions within and across temporal scales

Abstract: Summary1. Ecosystems at high altitudes and latitudes are expected to be particularly vulnerable to the effects of global change. We assessed the responses of littoral invertebrate communities to changing abiotic conditions in subarctic Swedish lakes with long-term data and compared the responses of subarctic lakes with those of more southern, hemiboreal lakes. 2. We used a complex systems approach, based on multivariate time-series modelling, and identified dominant and distinct temporal frequencies in the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 58 publications
3
37
0
1
Order By: Relevance
“…For example, the approach has been used to assess the resilience of subarctic lakes that are presumably threatened by global change, with vulnerability thought to increase with latitude [41]. However, Angeler et al [41] found that boreal and circumboreal lakes were both surprisingly robust to changing environmental conditions, because the distribution of functional feeding guilds of invertebrates were similar within and across scales for all lakes. However, managing specific scales within the lakes was deemed impossible because the cross-scale distributions reflected environmental change at broad spatial extents with slow dynamics that are difficult to control.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the approach has been used to assess the resilience of subarctic lakes that are presumably threatened by global change, with vulnerability thought to increase with latitude [41]. However, Angeler et al [41] found that boreal and circumboreal lakes were both surprisingly robust to changing environmental conditions, because the distribution of functional feeding guilds of invertebrates were similar within and across scales for all lakes. However, managing specific scales within the lakes was deemed impossible because the cross-scale distributions reflected environmental change at broad spatial extents with slow dynamics that are difficult to control.…”
Section: Discussionmentioning
confidence: 99%
“…In ecological systems, this is represented by species' functional traits, while in economies it might be the diversification of sectors contributing to GDP, or in anthropological studies the diversity of food resources available to populations. The next step is to analyze the distribution of functional attributes within and across the scale domains identified [41,72,78]. Are the functions non-randomly distributed?…”
Section: Tests Of the Cross-scale Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, many studies have determined the number of scales, as well as the species and their functional traits associated with each scale, by studying discontinuities in body mass distributions in animals (Allen and Holling 2008). Others have used time series modeling to identify scales of fluctuation frequencies based on abundance and biomass data (Angeler et al 2011(Angeler et al , 2013a. However, the cross-scale resilience model, i.e., within-and cross-scale functional redundancy, has been tested with limited data for a few terrestrial (Forys and Allen 2002, Allen et al 2005, Fischer et al 2007) and aquatic ecosystems (Angeler et al 2013a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Sin establecer aún una jerarquía o peso ponderado, ni sus relaciones de dependencia, a manera de una primera aproximación; se los entenderá como "capacidades y factores determinantes", dentro de este contexto, se pueden definir cuatro capacidades fundamentales que presentan los sistemas adaptativos complejos y que son inherentes a la resiliencia, así: la capacidad de aprendizaje; la capacidad de auto-organización, la adaptabilidad y la capacidad de transformación (Adger et al, 2005;Gall, 2013;Gunderson, 2000;Walker et al, 2004). De la misma manera se pueden identificar cuatro factores críticos que son determinantes para la resiliencia en un sistema adaptativo complejo, estos son: la redundancia, la diversidad, la modularidad y la apertura (Angeler et al,2013;Carpenter et al, 2012;Walker & Salt, 2012).…”
Section: Sistemas Adaptativos Complejos (Sac) Y La Resiliencia En Losunclassified